Economia maranhense de 1890 a 2010: superexploração e estado oligárquico como entraves ao desenvolvimento - PEREIRA FILHO, Jomar Fernandes (2016)
This research aims to make a reinterpretation of the economic formation of the state of Maranhão, using categories that are not present in traditional analyzes and with this, seeks to demonstrate that the roots of recurring socio-economic backwardness of the state, are not in legacy of eugenics catchphrases as “laziness of the people” and the “tropical weather”. The mainstream representatives usually have the economic formation of Maranhão as a natural succession of socioeconomic facts, without direct connection with the state, much less with global cycles of accumulation. The time gap achieved by the search extends 1890, beginning of the "industrial madness" until the first decade of xxi century. in the meantime evidence that the socio-economic backwardness of Maranhão is directly linked to patrimonial political practices of the oligarchic state will be sought, which gave institutional coverage for the exploitation of the labor force, which maintained a negative relationship with the growth of the domestic market and positive with the appellant technological backwardness that characterizes the local economy, historically dependent on external dynamic centers. This disastrous connection - overexploitation and oligarchic state - somehow can be credited to a reification put as simply "natural succession" of economic cycles, that tries to establish the thesis of capital naturalization. They are dialectically linked to unequal exchanges with higher productivity centers, with the global process of capital accumulation and collaborative subservience to these two factors by the local ruling classes.